La vagina dentada en un mito nivaclé: pérdidas como parte de la erotización corporal - Arley Fonseca, Mauricio (2014)
In nivacle myth “Water women”, from the naked corporality y uncultured, women motivate desire in men in order to approach to them. After anthropomorphous men capture them, they discover that those women have a particularity: they eat through vaginas, which are provided with sharped tooth. Men must practice rituals to be able to intercourse with them; if the practice doesn ́t happens through the ritual, the final will be violent, a real castration and not an opening and heritable erotic. The erotic ritual has as central practice: dancing, after performance those tooth will fall dawn from the vagina.